A clinical survey of dehydration during winter training in elite fencing athletes - Eda, N.; Azuma, Y.; Takemura, A.; Saito, T.; Nakamura, M.; Akazawa, N.; Yamamoto, M.; Naito, T.; Kasai, N.; Shimizu, K.; Aoki, Y.; Hoshikawa, M. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Fencing is suggested as one of the most dangerous sporting events in terms of dehydration because of the uniform and gear covering the entire body. We aimed to elucidate the change in hydration status before and after training in elite fencing athletes in winter along with the assessment of sex and fencing style differences. METHODS: Twenty-seven elite fencing athletes (14 males and 13 females) belonging to the Japanese National Team participated in this clinical survey. Dehydration status before and after winter training was assessed using body mass change, fluid intake, urine osmolarity, urine specific gravity (USG), and sodium, potassium, chlorine, and creatinine levels. RESULTS: More than half of the participants (59.3%) drank water and tea during training. The change rate of body mass (males vs. females, 1.61±0.82% vs. 0.45±0.68%, P<0.01; foil vs. epee, 2.25±0.45% vs. 1.16±0.72%, P<0.05) and sweating rate (males vs. females, 938±251 g/h vs. 506±92 g/h, P<0.01; foil vs. epee, 1136±156 g/h vs. 796±207 g/h, P<0.05) during training showed significant differences between sexes and fencing styles. Of all participants, 66.7% were dehydrated (USG=1.020), and 37.0% were seriously dehydrated (USG=1.030) before training. CONCLUSIONS: Fencing athletes may be susceptible to severe dehydration before training, even in winter. Additionally, males and foil fencers appear to be at a greater risk than females and epee fencers of developing dehydration during exercise.